PENGARUH SUBSTITUSI TEPUNG JAGUNG (Zea mays L.) DALAM PEMBUATAN COOKIES - Hardiyanti Hardiyanti; Kadirman Kadirman; Muhammad Rais (Universitas Negeri Makassar, 2016)
The study aims to determine the effect of substitution of corn flour in the production of cookies and cookies hedonic test results. Research carried out two stages. The first stage, the process of making corn flour. The second stage, of making cookies with concentration of wheat flour (100 g, 85 g, 80 g, 75 g) and cornstarch (0 g, 15 g, 20 g, 25 g). This study uses a completely randomized design (CRD), which consists of a single factor, namely the concentration of cornstarch 0 g, 15 g, 20 g and 25 g. Data were analyzed using analysis of variance (ANOVA) followed by a further test DMRT. In all aspects of testing the color, flavor, aroma and texture have F count> F table means that there is a real difference in each sample cookies experimental results. The results showed that the concentration of cornstarch similar in chemical quality of the water content of cookies as cookies. Cookies are most preferred treatment concentration C (25 g)